OPINIONS OF SECONDARY SCHOOL MUSIC TEACHERS ON THE USE OF EBA (EDUCATIONAL INFORMATION NETWORK): SAMPLES OF ŞANLIURFA - TABAK, Cihan; BOZ, Ümit (Atlas Journal, 2021)
With this research, it is aimed to determine the opinions of secondary school music teachers about the use of EBA. In line with the purpose of the research, the opinions of secondary school music teachers were taken by using the scanning model. The study group of the research consists of 22 music teachers working in Şanlıurfa in the 2021-2021 academic year. In order to collect data in the research, a semi-structured interview form was applied to the teachers. The data obtained as a result of the application were processed and descriptive analysis was made. As a result of the research, teachers related to EBA; They frequently use ’Live Lessons’, ’Lessons’ and ’My Page’ modules, EBA contributes to them and the students, they do not have access problems to EBA, but students have access problems, they prefer ’Mobile Application’ when using EBA, ’ It was concluded that they performed the ’Live Lesson’ module over the ’Zoom’ application and did not record it, that they did not find the music lesson contents in the EBA sufficient, that they produced content and made the contents produced outside of the EBA accessible to the students.